Food Demonstration Guide - Geralyn Sachs (EDIS)
This guide will help you plan and deliver a well-organized presentation that is entertaining and educational for your audience. A 4-H demonstration is a great way for you to share your passion and teach others about your 4-H food-related project work. Written by Geralyn Sachs, and published by the UF/IFAS Extension Florida 4-H Youth Development Program, June 2023.